2020
DOI: 10.1038/s41416-020-01052-8
|View full text |Cite
|
Sign up to set email alerts
|

EGFR as a stable marker of prostate cancer dissemination to bones

Abstract: Background Prostate cancer (PCa) is among the most commonly diagnosed malignancies in men. Although 5-year survival in patients with localised disease reaches nearly 100%, metastatic disease still remains incurable. Therefore, there is a need for markers indicating metastatic dissemination. Methods EGFR overexpression (EGFRover) was tracked in 1039 primary tumours, circulating tumour cells from 39 d’Amico high-risk patients and metastatic samples f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…3; c-Met: p=0.0053; p4EBP1: p=0.0019; pS6 p=0.0386). Increased c-Met and EGFR expression in bone metastases compared with primary prostate cancer, identified using the single cell mass cytometry, is consistent with previously reported findings 33,34 . This serves as additional confirmation of the specificity of the antibody panel used for single cell proteomic analysis of prostate cancer cells residing within the various tissue compartments.…”
Section: Main Textsupporting
confidence: 92%
“…3; c-Met: p=0.0053; p4EBP1: p=0.0019; pS6 p=0.0386). Increased c-Met and EGFR expression in bone metastases compared with primary prostate cancer, identified using the single cell mass cytometry, is consistent with previously reported findings 33,34 . This serves as additional confirmation of the specificity of the antibody panel used for single cell proteomic analysis of prostate cancer cells residing within the various tissue compartments.…”
Section: Main Textsupporting
confidence: 92%
“…Even more, castration leads to an increase in EGFR expression [96]. Supporting this crosstalk between AR and EGFR, several studies have found a significant relationship between EGFR expression and PCa progression [96][97][98][99][100][101][102]. In this study, no correlation was found in this direction.…”
Section: ãããmentioning
confidence: 49%
“…Upregulation of EGFR has been associated with prostate cancer progression and metastasis using various prostate cancer cell line model systems (DU145, PC-3, LNCaP and C4-2B) ( Gan et al, 2010 ; Day et al, 2017 ). Primary tumour EGFR overexpression correlated with migratory and metastatic phenotype of tumour cells in prostate cancer patients ( Nastały et al, 2020 ). While CTCs were detected in only 13% (5/39) of high-risk patients in this study, all CTCs were positive for EGFR using immunocytochemistry ( Nastały et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%